2013
DOI: 10.4172/jmso.1000109
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Fractures in an Early Stage of MS

Abstract: Objective: Low-energy (fragility) fractures of the distal forearm, femur, and vertebrae are usually associated with osteoporosis. There is an increased risk of fractures and low bone mineral density in patients with MS, even during the early stages of the disease. We evaluated the prevalence and features of low-energy fractures in a populationbased MS cohort residing in a region of Finland near the Arctic. Methods:The prevalence of fractures was determined in 491 patients who had been newly diagnosed with clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In our country, vitamin D deficiency is common both among patients with MS and the general population . A previous study from northern Finland suggested a high frequency of fractures in early stage of MS . The purpose of this study was to assess the prevalence of MS and the risk of osteoporotic fractures among Finnish patients with MS compared with age‐ and gender‐matched controls from a large hospital district in southwest Finland.…”
Section: Introductionmentioning
confidence: 98%
“…In our country, vitamin D deficiency is common both among patients with MS and the general population . A previous study from northern Finland suggested a high frequency of fractures in early stage of MS . The purpose of this study was to assess the prevalence of MS and the risk of osteoporotic fractures among Finnish patients with MS compared with age‐ and gender‐matched controls from a large hospital district in southwest Finland.…”
Section: Introductionmentioning
confidence: 98%